Increased adiposity by feeding growing rats a high-fat diet results in iron decompartmentalisation. Issue 10 (28th May 2020) - Lobo, Alexandre R.; Gaievski, Eduardo H. S.; de Mesquita, Carlos Henrique; De Carli, Eduardo; Teixeira, Pryscila Dryelle S.; Pereira, Rosa M. R.; Borelli, Primavera; de Sá, Lilian R. M.; Colli, Célia
Abstract: The present study reports the effects of a high-fat (HF) diet of over 8 weeks on the Fe status of growing rats. Tissue Fe levels were analysed by atomic absorption spectrophotometry, and whole-body adiposity was measured by dual-energy X-ray absorptiometry. Histopathology and morphometry of adipose tissue were performed. Liver homogenates were used for measuring ferroportin-1 protein levels by immunoblotting, and transcript levels were used for Fe genes measured by real-time PCR. Tissue Fe pools were fit to a compartmental biokinetic model in which Fe was assessed using fourteen compartments and twenty-seven transfer constants ( k j, i from tissue 'i' to tissue 'j') adapted from the International Commission on Radiological Protection (ICRP) 69. Ten k j, i were calculated from the experimental data using non-linear regression, and seventeen were estimated by allometry according to the formula k_i, j = a × M^b . Validation of the model was carried out by comparing predicted and analysed Fe pool sizes in erythrocytes, the liver and the spleen. Body adiposity was negatively associated with serum Fe levels and positively associated with liver Fe stores. An inferred increase in Fe transfer from bone marrow to the liver paralleled higher hepatic Fe concentrations and ferritin heavy-chain mRNA levels in the HF diet-fed animals, suggesting that liver Fe accumulation occurred at least in part due to a favoured liver erythrocyte uptake. If this feeding condition was to be prolonged, impaired Fe decompartmentalisation may occur, ultimately resulting in dysmetabolic Fe overload.